Pengaruh Pasta Gigi Ekstrak Daun Sukun (Artocarpus altilis (Park.) Fosberg.) Terhadap Hambatan Pertumbuhan Streptococcus mutans - Thifal, Ghazalah, drg. Mahmud Kholifa, MDSc, drg. Juwita Raditya Ningsih (2016)
Dental caries is the most common oral disease caused by Streptococcus mutans. Dental caries can be mechanically and chemically prevented by tooth brushing with toothpaste. The use of triclosan as antibacterial agentin toothpaste has some drawbacks, among others, for instance produce toxic pollution of the environment and trigger allergies. The use of herbal ingredients in medicine and pharmacology are considered have minor side effects than chemical based antibacterial agents. Leaves of breadfruit (Artocarpusaltilis (Park.)Fosberg.) is one of the herbal ingredients which can inhibit the growth of bacteria because of its containing active substances such as alkaloids, flavonoids, tanins and phenols. The aim of this study were to determine the antibacterial effect of toothpaste breadfruit leaves extract on the growth of Streptococcus mutans bacteria and to determine which concentration of breadfruit leaves extract in toothpaste that provides the greatest antibacterial effect. The research was true experimental laboratory study with post-test only control group design. The method of this research used Kirby bauser that treatment groups with different treatments of breadfruit leaves extract toothpaste 5%, 10%, 20%, 40% 80% concentration, toothpaste with triclosan as positive control, and toothpaste with aquadest as negative control. The results of this study reveal that a mean diameter of inhibitory zone toothpaste breadfruit leaves extract concentrations of 5%, 10%, 20%, 40%, 80%, positive and negative control, respectively, are 4.99 mm, 7.55 mm, 10.07 mm, 12.89 mm, 16.69 mm, 21.16 mm and 0 mm. It is shown that inhibitory zone was increasing with the increasing breadfruit leaves extract toothpaste concentrations. The result of one way Anova test showed significant value p = 0,000 (p < 0,05). Post Hoc LSD test showed value p= 0.000 (p<0.05), which means breadfruit leaves extract toothpaste various concentrations is effective for antibacterial agent compared with negative control. The highest mean of inhibitory zone for breadfruit leaves extracttoothpaste is 16,69mm in concentration 80% (strength antibacterial agent), although mean of inhibitory zone positive control is still better 21,16mm. The conclusion of this study breadfruit leaf extract in toothpaste at various concentrations show antibacterial effect on the growth of Streptococcus mutans and breadfruit leaf extract in toothpaste concentration of 80% has the greatest inhibition to growth of Streptococcus mutans. Keywords: Toothpaste, breadfruit leaves (Artocarpus altilis (Park.) Fosberg.), dental caries, growth inhibition, Streptococcus mutans